Solving mathematical word problem using scaffolding approach / Najihah Ali - Ali, Najihah (2012)
The developed courseware was designed to help student in standard one in primary school to solve mathematical word problem using scaffolding approach. The courseware is based on Kurikulum Standard Sekolah Rendah (KSSR) which also can be use as a teaching material at school. Scaffolding has been chosen as the method of learning mathematical word problem because it is believed to have a potential to enhance mathematics learning. Through the study about constructivism as the learning theory for mathematics education, scaffolding is the best teaching strategy that can help to implement constructivism. In these lessons, students were always encouraged to explain and justify their solutions. Students are hoped to be more engaging while answering the question provided.